VEGAS2: Software for More Flexible Gene-Based Testing. (18th December 2014) - Mishra, Aniket; Macgregor, Stuart
Abstract : Gene-based tests such as ve rsatile g ene-based a ssociation s tudy (VEGAS) are commonly used following per-single nucleotide polymorphism (SNP) GWAS (genome-wide association studies) analysis. Two limitations of VEGAS were that the HapMap2 reference set was used to model the correlation between SNPs and only autosomal genes were considered. HapMap2 has now been superseded by the 1, 000 Genomes reference set, and whereas early GWASs frequently ignored the X chromosome, it is now commonly included. Here we have developed VEGAS2, an extension that uses 1, 000 Genomes data to model SNP correlations across the autosomes and chromosome X. VEGAS2 allows greater flexibility when defining gene boundaries. VEGAS2 offers both a user-friendly, web-based front end and a command line Linux version. The online version of VEGAS2 can be accessed throughhttps://vegas2.qimrberghofer.edu.au/ . The command line version can be downloaded fromhttps://vegas2.qimrberghofer.edu.au/zVEGAS2offline.tgz . The command line version is developed in Perl, R and shell scripting languages; source code is available for further development.